Optimal Cut-Off Value of the Superior Articular Process Area as a Morphological Parameter to Predict Lumbar Foraminal Stenosis - Tae-Ha Lim; Soo Il Choi; Hyung Rae Cho; Keum Nae Kang; Chang Joon Rhyu; Eun Young Chae; Young Su Lim; Yongsoo Lee; Young Uk Kim (Pain Research and Management)
Background. We devised a new morphological parameter called the superior articular process area (SAPA) to evaluate the connection between lumbar foraminal stenosis (LFS) and the superior articular process. Objective. We hypothesized that the SAPA is an important morphologic parameter in the diagnosis of LFS. Methods. All patients over 60 years of age were included. Data regarding the SAPA were collected from 137 patients with LFS. A total of 167 control subjects underwent lumbar magnetic resonance imaging (MRI) as part of a routine medical examination. We analyzed the cross-sectional area of the bone margin of the superior articular process at the level of L4-L5 facet joint in the axial plane. Results. The average SAPA was 96.3±13.6 mm2 in the control group and 128.1±17.2 mm2 in the LFS group. The LFS group was found to have significantly higher levels of SAPA (p<0.001) in comparison to the control group. In the LFS group, the optimal cut-off value was 112.1 mm2, with 84.4% sensitivity, 83.9% specificity, and AUC of 0.94 (95% CI: 0.91–0.96). Conclusions. Higher SAPA values were associated with a higher possibility of LFS. These results are important in the evaluation of patients with LFS.